Rethinking the Robe River dispute 1986-7 – de-unionisation in Australia's Pilbara iron ore industry in the early neoliberal period. (4th March 2022) - Vassiley, Alexis
ABSTRACT: The Robe River dispute of 1986-7 was the anti-union New Right's first attempt to defeat union power at a large workforce in Australia. This occurred during an industrial relations period of 'cooperation' between unions, employers and government under Australia's social contract – the Accord. The dispute was also the first successful attack of its kind in Western Australia's highly strike-prone Pilbara iron ore industry. Despite its subsequent victory, Robe River management was in a weak position during the dispute, and successful industrial action was a viable prospect. Unionists at the Robe River company were the most militant in the industry. Yet after a six-month dispute, union power was no longer. This article argues union officials' strategy of avoiding industrial action at all costs led to defeat. This strategy was adopted in the context of firstly, the social contract promising peace between unions and employers, secondly, the Pilbara industrial relations environment of strong localised grassroots networks of union power, conflict with metropolitan-based union officials, and worker encroachment on managerial prerogative, and thirdly, the contingent conservatism of the trade union bureaucracy. Union power in the Pilbara had underlying political weaknesses, meaning that an alternative strategy to that adopted by the union bureaucracy did not win out.